Analisis Jabatan sebagai Instrumen Strategis dalam Pengelolaan Sumber Daya Manusia - Alivia Ummi Jamilah; Siti Komariyah; Abd. Fiqrial Akbar; Nur Alif Bahtiar; Mu’alimin Mu’alimin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Job analysis serves as a strategic instrument in human resource management (HRM), forming the basis for organizational structure design, job descriptions and specifications, and supporting employee evaluation and development processes. This study employs a literature review approach involving 50 articles, narrowed down to 5 core sources to explore the critical role of job analysis. Findings indicate that job analysis not only enhances employee performance and job satisfaction, but also supports optimal placement based on competencies and personality profiles such as the DISC approach. Job analysis has proven effective in the education sector and holds broader potential for implementation across various industries.